The Sedative Effects of Inhaled Nebulized Dexmedetomidine on Children: A Systematic Review and Meta-Analysis - Lin, Jun; Wu, Chujun; Zhao, Dizhou; Du, Xuhang; Zhang, Wangzhi; Fang, Jieyu (Frontiers in Pediatrics, 2022)
Background: Children that need surgery and medical examinations are often uncooperative, and preoperative sedation is necessary. We aimed to assess the safety and efficacy of inhaled nebulized dexmedetomidine in children for sedation that underwent medical examinations or surgery. Methods: We systematically searched PubMed, Web of science, Embase, and Cochrane library, for randomized controlled trials of Intranasal dexmedetomidine using a spray or a mucosal atomization device in children undergoing examination or elective surgery. We included all studies that analyzed the sedation efficiency of intranasal dexmedetomidine in children. Results: fifteen studies with 1779 pediatric patients were included. Compared to other sedation treatments, inhaled nebulized dexmedetomidine showed similar sedation satisfaction (risk ratio RR: 1.01; 95% confidence interval [CI]: 0.89 to 1.15; P=0.87; I2=67%). there was also no statistical difference in the success rate of separation from parents (RR: 0.96; 95% CI: 0.82 to 1.12; P=0.58; I2=67%), and mask acceptability (RR: 1; 95% CI: 0.83 to 1.20; P=0.99; I2=35%). But it is worth mentioning that nebulized dexmedetomidine combined with ketamine provided better sedation satisfaction (RR: 0.69; 95% CI: 0.49 to 0.96; I2=49%) and more satisfactory separation from parents (RR: 0.85; 95% CI: 0.74 to 0.97; I2=0%). Moreover, nebulized dexmedetomidine reduced the occurrences of nausea and vomiting (RR: 0.28; 95% CI: 0.15 to 0.51; P<0.01; I2=10%) and emergence agitation (RR: 0.30; 95% CI: 0.18 to 0.49; P<0.01; I2=0%). There are no hypotension or arrhythmia reported that required intervention in all articles. Conclusion: Compared to other premedication treatments, inhaled nebulized dexmedetomidine provided equivalent sedation satisfaction for the examination or preoperative sedation of children, but it reduced the occurrences of emergence agitation and postoperative nausea and vomiting.